Robustness of the EUROPEP questionnaire as regards data quality, reliability, and construct validity: The Greek experience before and after the economic crisis. Issue 8 (August 2020) - Vova-Chatzi, C.; Symvoulakis, E.; Parpoula, C.; Sbarouni, V.; Lionis, C.
Highlights: We first evaluate Greek EUROPEP's psychometric properties pre- and post-crisis. Second, we evaluate EUROPEP's robustness in different economic contexts. We then evaluate its ability to detect differences in different economic contexts. The Greek EUROPEP remains relevant post-crisis despite new economic conditions and useful to policymakers. The Greek EUROPEP reliably evaluates people's needs after the recent Primary Health Reform. Abstract: Objectives: To assess the data quality, reliability, and construct validity of the Greek EUROPEP and to examine the instrument's robustness in terms of its psychometric properties in a pre- and post-economic crisis period. Methods: Taking into account the two key factors that affect the accuracy and quality of survey data, that is the representativeness of the sample selected from the population, and the response rate, four hundred ninety-two and five hundred thirty-two patients (492 and 532 patients) pre- and post-crisis, respectively, consulting GPs at 16 Primary Health Care Centers (PHCCs) in Greece were invited to complete the Greek EUROPEP. We assessed item missing, ceiling and floor effects, and used factor analysis to assess the structure of the 23 items of the EUROPEP. Scales were tested for reliability and construct validity. We further examined if the scales of EUROPEP need to be refined, taking into account the external validity across economic crises. Results: Factor analysis identified three groups of questions that formed scales with satisfactory internal consistency reliability, and validity. The clinical behavior scale, the support, and services scale, and the organization of care scale, all met the criterion of 0.7 for Cronbach's alpha. All scales were found to have a significant correlation with the majority of the examined variables. Moreover, the EUROPEP was found to be robust in effectively detecting differences in patients' views over time in different economic contexts. Conclusions: The study identified three scales in the Greek EUROPEP-questionnaire with satisfactory psychometric properties, and its Greek version could be used in the recent primary health care (PHC) reform in this country.